Did Fukushima matter?: empirical evidence of the demand for climate protection in Germany - Gallier, Carlo (Discussion paper)
This paper investigates the extent to which the Fukushima Daiichi nuclear disaster of March 2011 has had an impact on the private demand for climate protection in Germany. Data are taken from two framed field experiments (Löschel et al. 2013a, b) conducted before and after the disaster. We find that the demand for climate protection in the experiment after the nuclear disaster is significantly higher than in the experiment before the disaster. -- Experimental economics ; demand for climate protection
Literaturverz. S. 9 - 10